Enhancing Speaking Skills of Non-English Major Students: Evaluating the Impact of Sociodramatic Games - Nuraini, Siti Aufadiyah; Sudiran, Sudiran; Hartono, Hartono (Universitas Hamzanwadi, 2023)
This study examines the efficacy of sociodrama games as a method for improving English speaking skills among EFL (English as a Foreign Language) students in Indonesia, specifically in accounting and financial institutions departments. The research utilizes a descriptive qualitative design to explore the implementation of sociodrama games by an English teacher and assess their impact on students' speaking abilities. Participants include one English teacher and three eleventh-grade students specializing in accounting and financial institutions, selected through purposive sampling. Data were gathered via observations and interviews and analyzed using Miles and Huberman’s interactive and continuous techniques for qualitative data analysis. The results reveal that sociodrama games significantly enhance students' motivation, self-confidence, active participation, and speaking skills in English language learning. Particularly noteworthy is the progress observed at SMKN 1 Rejotangan. The study concludes that sociodrama games are a compelling and effective teaching strategy, substantially benefiting students' development in English speaking proficiency.